Ethnoveterinary medicines used for ruminants in British Columbia, Canada - Brauer Gerhard; Khan Tonya; Turner Nancy; Lans Cheryl; Boepple Willi (BMC, 2007)
Abstract Background The use of medicinal plants is an option for livestock farmers who are not allowed to use allopathic drugs under certified organic programs or cannot afford to use allopathic drugs for minor health problems of livestock. Methods In 2003 we conducted semi-structured interviews with 60 participants obtained using a purposive sample. Medicinal plants are used to treat a range of conditions. A draft manual prepared from the data was then evaluated by participants at a participatory workshop. Results There are 128 plants used for ruminant health and diets, representing several plant families. The following plants are used for abscesses: Berberis aquifolium/Mahonia aquifolium Echinacea purpurea, Symphytum officinale, Bovista pila, Bovista plumbea, Achillea millefolium and Usnea longissima. Curcuma longa L., Salix scouleriana and Salix lucida are used for caprine arthritis and caprine arthritis encephalitis.Euphrasia officinalis and Matricaria chamomilla are used for eye problems. Wounds and injuries are treated with Bovista spp., Usnea longissima, Calendula officinalis, Arnica sp., Malva sp., Prunella vulgaris, Echinacea purpurea, Berberis aquifolium/Mahonia aquifolium, Achillea millefolium, Capsella bursa-pastoris, Hypericum perforatum, Lavandula officinalis, Symphytum officinale and Curcuma longa. Syzygium aromaticum and Pseudotsuga menziesii are used for coccidiosis. The following plants are used for diarrhea and scours: Plantago major, Calendula officinalis, Urtica dioica, Symphytum officinale, Pinus ponderosa, Potentilla pacifica, Althaea officinalis, Anethum graveolens, Salix alba and Ulmus fulva. Mastitis is treated with Achillea millefolium, Arctium lappa, Salix alba, Teucrium scorodonia and Galium aparine. Anethum graveolens and Rubus sp., are given for increased milk production.Taraxacum officinale, Zea mays, and Symphytum officinale are used for udder edema. Ketosis is treated with Gaultheria shallon, Vaccinium sp., and Symphytum officinale. Hedera helix and Alchemilla vulgaris are fed for retained placenta. Conclusion Some of the plants showing high levels of validity were Hedera helix for retained placenta and Euphrasia officinalis for eye problems. Plants with high validity for wounds and injuries included Hypericum perforatum, Malva parviflora and Prunella vulgaris. Treatments with high validity against endoparasites included those with Juniperus communis and Pinus ponderosa. Anxiety and pain are well treated with Melissa officinalis and Nepeta caesarea.